Long-term changes in cognitive bias and coping response as a result of chronic unpredictable stress during adolescence - Chaby, Lauren; Cavigelli, Sonia; White, Amanda; Wang, Kayllie; Braithwaite, Victoria (Frontiers in Human Neuroscience, 2013)
Animals that experience adverse events in early life often have life-long changes to their physiology and behavior. Long-term effects of stress during early life have been studied extensively, but less attention has been given to the consequences of negative experiences solely during the adolescent phase. Adolescence is a particularly sensitive period of life when regulation of the glucocorticoid “stress” hormone response matures and specific regions in the brain undergo considerable change. Aversive experiences during this time might, therefore, be expected to generate long-term consequences for the adult phenotype. Here we investigated the long-term effects of exposure to chronic unpredictable stress during adolescence on adult decision making, coping response, cognitive bias, and exploratory behavior in rats. Rats exposed to chronic unpredictable stress (e.g. isolation, crowding, cage tilt) were compared to control animals that were maintained in standard, predictable conditions throughout development. Unpredictable stress during adolescence resulted in a suite of long-term behavioral and cognitive changes including a negative cognitive bias (F1,12 = 5.000, P < 0.05), altered coping response (T1,14 = 2.216, P = 0.04), and accelerated decision making (T1,14 = 3.245, P = 0.01). Exposure to chronic stress during adolescence also caused a short-term increase in boldness behaviors; in a novel object test 15 days after the last stressor, animals exposed to chronic unpredictable stress had decreased latencies to leave a familiar shelter and approach a novel object (T1,14 = 2.240, P = 0.04; T1,14 = 2.419, P = 0.03, respectively). The results showed that stress during adolescence has long-term impacts on behavior and cognition that affect the interpretation of ambiguous stimuli, behavioral response to adverse events, and how animals make decisions. Stress during adolescence also induced short-term changes in the way animals moved around a novel environment.